Reconstruction of railroads at Klaipéda da National Seaport: Local Health Impact Assessment Case in Lithuania (Italian Journal of Public Health, 2007)
Background: Introduction of health impact assessment (HIA) as a national legal requirement for planned economic activity projects in 2002 and the further development of related procedures and methodological requirements has boosted the number of HIAs carried out both as an integrated part of environmental impact assessment (EIA) procedures as well as an independent activity. Most of HIAs have been conduct for local projects. The HIA for the reconstruction of the southern section of the railroads in Klaip da National Seaport is one of the local HIAs in Lithuania carried out as an independent procedure. Methods: The HIA for the reconstruction of the southern section of the railroads in Klaipda National Seaport was carried out following the national legal procedure for the cases not foreseen in the Law on Environmental Impact Assessment of Planned Economic Activity and the national HIA methodological regulations. The HIA included a literature review, analysis of related technical documentation, data on existing and estimated air pollution and environmental noise levels and possible health consequences, analysis of local demographic and health statistics; interviews with the residents living in proximity of the planned activity, analysis of public complaints on existing activities at Klaip da National Seaport, site visit and round table discussions with the proponent of the planned activity, planning company and representatives of the public health authority. The standard or intermediate type of perspective HIA was applied. Results: The HIA report has pointed out noise, vibration, ambient air pollution, psychological factors as related to possible negative impact on health of residents living in the mostly exposed locations. Interviews with inhabitants living in proximity of the planned activity have shown that majority of them knew nothing about the reconstruction plans. Recommendations were provided in the report how to minimise existing and prevent newly emerging negative health impacts from the planned economic development related to ambient air and environmental noise pollution as well as recommendations for communication improvement. with the residents. Conclusion: The HIA provided the proponent of planned activity, as well as the regional public health authority and the concerned public with relevant information on the main health determinants and possible health impacts of the planned reconstruction of the railway segment. HIA recommendations stimulated the proponent to agree on additional measures reducing negative health impact of the planned activity. This case of HIA also revealed some strengths and weaknesses of the overall HIA framework in Lithuania.
Keywords: Local health impact assessment cas; national legal requirements for HIA; planned economic